2014
DOI: 10.2196/jmir.3539
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of a Web-Based Guided Self-Help Intervention for Employees With Depressive Symptoms: Randomized Controlled Trial

Abstract: BackgroundDepressive disorders are highly prevalent in the working population and are associated with excessive costs. The evidence for effective worker-directed interventions for employees with depressive symptoms is limited. Treating employees with depressive symptoms via the Internet before they report sick from work could be beneficial and cost saving.ObjectiveIn this study, we tested the effectiveness over the period of 1 year of a Web-based guided self-help intervention, called Happy@Work, for employees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 64 publications
(68 reference statements)
4
56
1
2
Order By: Relevance
“…As two studies were published in two different journals, with both papers reporting the same intervention, it was decided to only include the first publication of these papers19 and exclude the later one 20. Another study discussed short-term21 and long-term22 effects of the same data and intervention in two different papers, and therefore were considered as one study. Table 1 and table 2 summarise the description of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…As two studies were published in two different journals, with both papers reporting the same intervention, it was decided to only include the first publication of these papers19 and exclude the later one 20. Another study discussed short-term21 and long-term22 effects of the same data and intervention in two different papers, and therefore were considered as one study. Table 1 and table 2 summarise the description of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Kolejnym programem jest "Happy@Work", interwencja internetowa zaprojektowana dla pracowników cierpiących z powodu objawów depresji [25]. Skła-da się ona z 6 lekcji opartych na założeniach CBT.…”
Section: Internetowe Interwencje Psychologiczneunclassified
“…Na podstawie tych wyników można sugerować, że zarówno interaktywne ćwiczenia (moduł wzmacniający przekonania o własnej skuteczności), jak i prezentacja materiałów edukacyjnych dotyczą-cych radzenia sobie z pośrednią ekspozycją na traumę i stresem w pracy (moduł edukacyjny) skutecznie oddziałują na poziom obu zmiennych wynikowych. Także wyniki innych badań potwierdzają, że internetowe interwencje bazujące na różnych podejściach -takich jak CBT [25] czy psychologia pozytywna [24] -są skuteczne w zmniejszaniu nasilenia objawów wypalenia zawodowego i wzmacnianiu zaangażowania w pracę.…”
Section: Omówienieunclassified
“…A recent randomized trial found Ebert et al moderate effect sizes with regard to the reduction of depressive symptoms among stressed teachers (6,14), whereas another trial did not find beneficial effects of a problem-solving training on depression or work-related outcomes (15,16). So far, randomized controlled trials (RCT) on internet-based SMI show mixed results with some studies reporting significant results with moderate effects sizes on perceived stress (17)(18)(19) and others yielding non-significant outcomes (20,21).…”
mentioning
confidence: 99%